Improving Al-Qur'an Reading Ability through the Introduction of Letter Achorjul at TPQ Al-Anwariyyah - Nurbaiti, Trianda; Rosyadi, Abdu Rahmat (Jurnal Pengabdian Nusantara, 2023)
This study focuses on how the application of the sorogan method in learning to read makharijul letters and whether there is an increase in the ability to read makharijul letters after using the Sorogan method. The method used in this study is the PAR (Participatory Action Research) approach. The results of this study are that the application of the sorogan method is carried out in groups and students experience an increase in the ability to read the Qur'an through the introduction of makhorijul letters through the sorogan method. This research has an impact on increasing students' ability to read the Qur'an. Students learn to read the Qur'an easily through the sorogan method.